A study on the ultimate mechanical properties of middle-aged and elderly human aorta based on uniaxial tensile test - Chen, Hongbing; Zhao, Minzhu; Li, Yongguo; Wang, Qi; Xing, Yu; Bian, Cunhao; Li, Jianbo (Frontiers in Bioengineering and Biotechnology, 2024)
The mechanical properties of the aorta are particularly important in clinical medicine and forensic science.To study the influence of various factors (age, gender, test direction, anatomical location, and pathological characteristics) on the mechanical properties and thickness of the aorta.In this study, a total of 24 aortas (age range: 54-88 years old) were collected, one hundred and seventy-four dog-bone-shaped samples were made, and then the uniaxial tensile test was run, finally, pathological grouping was performed through histological staining.Atherosclerotic plaques were mainly distributed near the openings of blood vessel branches. The distribution was most severe in the abdominal aorta, followed by the aortic arch.Aortic atherosclerosis was a more severe trend in the male group. In the comparison of thickness, there were no significant differences in age (over 50 years) and test direction, the average thickness of the aorta was greater in the male group than the female group and decreased progressively from the ascending aorta to the abdominal aorta. Comparing the mechanical parameters, various parameters are mainly negatively correlated with age, especially in the circumferential ascending aorta (εp "Y = -0.01402*X + 1.762, R²= 0.6882", εt "Y = -0.01062*X + 1.250, R²= 0.6772"); the parameters of males in the healthy group were larger, while the parameters of females were larger in atherosclerosis group; the aorta has anisotropy, the parameters in the circumferential direction were greater than those in the axial direction; the parameters of the ascending aorta were the largest in the circumferential direction, the ultimate stress [σp "1.69(1.08,2.32)"] and ultimate elastic modulus [E2"8.28(6.67,10.25)"] of the abdominal aorta were significantly larger in the axial direction; In the circumferential direction, the stress [σp "2.2(1.31,3.98)", σt "0.13(0.09,0.31)"] and ultimate elastic modulus (E2 "14.10±7.21") of adaptive intimal thickening were greater than those of other groups, the strain (εp "0.82±0.17", εt "0.53±0.14") of pathological intimal thickening was the largest in the pathological group.The present study systematically analyzed the influence of age, sex, test direction, anatomical site, and pathological characteristics on the biomechanical properties of the aorta, described the distribution of aortic atherosclerosis, and illustrated the characteristics of aortic thickness changes.